Case Report: Persistency Pneumococcal Polysaccharide in Cerebrospinal Fluid During a Post Pneumococcal Chronic Aseptic Meningitis: Coincidental or (Auto-)Inflammatory Embers - Ladeveze, Manon; Dumont, Yann; Boursier, G.; Batteux, Frederic; Mahe, Perrine; Bensimon Borrull, Aurelie; Sarrabay, Guillaume; Bollore, Karine; Tuaillon, Edouard; Godreuil, Sylvain; Jeziorski, Eric (Frontiers in Pediatrics, 2022)
We report the case of a nine-months-old boy that has presented a steroid-dependent post-pneumococcal chronic aseptic meningitis was associated with persistence of pneumococcal cell wall components in cerebrospinal fluid during more than 20 month. Suggesting that this antigenic persistence could be involved in post-infectious manifestations through innate immunity response.